Habitat for health: exploring the impact of rural human settlements on elderly behaviors and physical function across gender in Sichuan, China - Zhenhua Zheng; Linquan Chen; Yuetong Wang; Yilin Jin; Yanmei Liu (Journal of Asian Architecture and Building Engineering)
Global population aging has intensified health challenges for older adults, yet research gaps persist on how rural human settlements mechanically influence elderly health through gender-differentiated perspectives. Leveraging data from the 2024 Rural Environment and Elderly Health Survey (1,084 seniors across 42 counties in Sichuan Province, China), this study employs structural equation modeling to analyze the complex relationships among rural human settlements, walking exercise, neighborhood interaction, and physical function of older adults. Results demonstrate that improved rural human settlements, regular walking, and active social interactions play a collective role in enhancing elderly physical function. Both physical and social behaviors mediate rural human settlements impacts, with social behaviors showing stronger mediation. Notably, the study indicates that rural human settlements exert a more pronounced impact on the physical function of elderly women. While physical activities primarily enhance the physical function of elderly men, the well-being of elderly women is significantly more influenced by social behaviors. The findings advocate prioritizing rural settlement improvements in Sichuan through activity-friendly village spaces and gender-sensitive environmental planning. This study offers actionable insights for enhancing elderly health outcomes while contributing empirical evidence from China to inform global aging initiatives and rural development strategies in developing regions.